1991
DOI: 10.1080/08927019109378208
|View full text |Cite
|
Sign up to set email alerts
|

On saliva structures

Abstract: Structures in human saliva were demonstrated using flash freezing, sectioning, fixing/staining and microscopic examinations. The microarchitecture and staining patterns of these structures and interactions with cellular material indicate the presence of the following salivary compartments: (1) a continuous water-based electrolyte, (2) a continuous scaffold-like network of amphiphilic macromolecules, (3) network cores with e.g. EGF/NGF-activities, and (4) dispersed lipoid droplets. Through some acellular ingest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…2 This generally pessimistic view is challenged by a plethora of prior studies of salivary mucins, very similar to cervical glycoproteins, that do illustrate structural and functional changes (some of which co-vary with menstrual cycle days) with modified compositions. 3,4,5,6,7,8,9,10,11,12,13 In addition to observing P/S relationships over several menstrual cycles, the investigation repeated examination of ratios within 24-hour time-spans to determine whether the variance in sampling times altered the sample results and to identify the amount of change that normally occurs in the P/S ratio on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…2 This generally pessimistic view is challenged by a plethora of prior studies of salivary mucins, very similar to cervical glycoproteins, that do illustrate structural and functional changes (some of which co-vary with menstrual cycle days) with modified compositions. 3,4,5,6,7,8,9,10,11,12,13 In addition to observing P/S relationships over several menstrual cycles, the investigation repeated examination of ratios within 24-hour time-spans to determine whether the variance in sampling times altered the sample results and to identify the amount of change that normally occurs in the P/S ratio on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…Whether co‐aggregation occurs in vivo , or only represents a model for co‐adhesion is an open question (3, 4). It has been argued that the concentration of co‐aggregating bacterial partners in saliva is too low for co‐aggregation to occur, while in addition, the fibrinous structure of saliva (5) restricts bacterial mobility. Brownian motion dynamics demonstrated that co‐adhesion contributes to the formation of ordered structures in dental plaque and is consequently more likely to occur in vivo (1).…”
mentioning
confidence: 99%